Weight loss drugs and lifestyle modification: Perceptions among a diverse adult sample. Issue 3 (March 2017) - Xing, S.; Sharp, L.K.; Touchette, D.R.
Highlights: Views on prescription, OTC and herbal supplements for weight loss varied greatly. Perceived risk and efficacy influenced attitudes towards weight loss drugs. Many believed that herbal supplements are natural and safe to use for weight loss. Drugs were perceived as a short-cut and not a long-term weight management option. Abstract: Objectives: Explore how adults from diverse racial and socioeconomic backgrounds perceive the use of weight loss drugs (prescription, over-the counter, herbals and supplements) and lifestyle modification. Methods: Individual, face-to-face, semi-structured interviews were conducted with persons presenting to an academic hospital-affiliated outpatient pharmacy serving ethnic minorities and low income individuals. Results: Fifty persons were interviewed, including 21 African Americans, 11 Hispanics and 17 low-income individuals (annual income <20, 000), of whom 33 self-reported as overweight or obese. Ever-users (14/50) and nonusers (36/50) of weight loss drugs expressed a belief in the importance of diet and exercise, but were not necessarily doing so themselves. Fear of side effects and skepticism towards efficacy of drugs deterred use. Some expressed concern over herbal product safety; others perceived herbals as natural and safe. Drugs were often viewed as a short-cut and not a long-term weight management solution. Conclusion: A range of concerns related to the safety and efficacy of weight loss drugs were expressed by this lower income, ethnically diverse population of underweight to obese adults. Practice implications: There is need and opportunity for healthcare providers to provide weight loss advice and accurate information regarding the safety and efficacy of various types of weight loss approaches.